EFEKTIVITAS MODEL NUMBERED HEADS TOGETHER DALAM MENINGKATKAN FOKUS DAN KEAKTIFAN BELAJAR SISWA KELAS 8 PADA PELAJARAN FIQIH - Afifah, Hana Nur (EDUCATIVA, 2024)
By using the Numbered Heads Together (NHT) learning model through Classroom Action Research (CAR), this study aims to improve the concentration and learning participation of 8th grade students at MTs Nurul Ikhlas in the subject of fiqh. This study was conducted in two stages using qualitative and quantitative methods. Observation, interviews, questionnaires, document recording, and learning outcome tests are various methods used to collect data. It has been proven that the implementation of the NHT model can improve students' active participation and their learning performance. In cycle I, the score obtained by the teacher reached 18 (64.2), with an average class score of 75 and a percentage of learning success reaching 50%. In cycle II, the class test score increased to 77.5 and the percentage of learning completion reached 75%. Therefore, this model can be used as an option for fiqh learning in junior high schools/MTs.